2019
DOI: 10.1111/vcp.12708
|View full text |Cite
|
Sign up to set email alerts
|

Feline Sporothrix spp. detection using cell blocks from brushings and fine‐needle aspirates: Performance and comparisons with culture and histopathology

Abstract: Background: Sporotrichosis is an emerging zoonotic mycosis that presents as a cutaneous lymphatic or disseminated disease, caused by fungi from the Sporothrix schenkii (S schenkii) clinical clade. Its importance is growing, primarily due to an outbreak that occurred in Brazil, affecting mainly cats and people.Objectives: In Brazil, an S schenkii diagnosis is often made using cultures, which allows genus identification and sufficient growth to perform molecular biology testing.Despite its advantages, fungal cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 10 publications
0
12
0
1
Order By: Relevance
“…These structures measure 3-5 lm in diameter and 5-9 lm in length and are surrounded by a clear halo. Recently, Gonsales et al reported the high sensitivity (97.5%) of using cell block cytology (imprint) as an efficient and rapid tool for diagnosing sporotrichosis in cats, particularly during epidemics [214].…”
Section: Improving Early Diagnosis Is the Key To Tackle Sporotrichosismentioning
confidence: 99%
“…These structures measure 3-5 lm in diameter and 5-9 lm in length and are surrounded by a clear halo. Recently, Gonsales et al reported the high sensitivity (97.5%) of using cell block cytology (imprint) as an efficient and rapid tool for diagnosing sporotrichosis in cats, particularly during epidemics [214].…”
Section: Improving Early Diagnosis Is the Key To Tackle Sporotrichosismentioning
confidence: 99%
“…It is noteworthy that in order to have therapeutic monitoring using cytopathological examination, it should be collected a sequential exudate from the same skin lesion for quantitative comparison of the fungal burden. A cell block cytology was recently described as an efficient tool to diagnose sporotrichosis in cats [98].…”
Section: Direct Microscopic Examinationmentioning
confidence: 99%
“…Cases of human sporotrichosis have been reported in 14 of 26 Brazilian states, and the southern and southeast regions of Brazil have the highest incidence of human cases . According to Pereira et al (2014), sporotrichosis is considered a neglected disease and was a serious public health problem in Rio de Janeiro; from 1997 to 2011, 4118 human cases diagnosed at the INI/FIOCRUZ (Instituto Nacional de Infectologia Evandro Chagas/ Fundação Oswaldo Cruz), the main reference center for the treatment of this ringworm in Brazil (Silva et al, 2013;Gremião et al, 2015). In the last 3 years the city of Guarulhos has registered more than 1500 cases in cats, resulting in a status of "compulsory notification".…”
mentioning
confidence: 99%
“…The definitive diagnosis depends on the isolation of the etiologic agent in culture (Silva et al, 2015). Other methodologies proposed for diagnosis are cytopathology (Pereira et al, 2011), histopathology (Miranda et al, 2013), serology (Fernandes et al, 2011), species determination by polymerase chain reaction of fungal isolation (Rodrigues et al, 2015) and cell block cytology (Gonsales et al, 2019). The aim of this study was to detect and identify the species of Sporothrix in cats with lesions from an endemic area and for whom sporotrichosis was part of the differential diagnosis (city of Guarulhos) and compare this method with the reference methodology, fungal culture, considering the following variables: type of injury (dry or wet) and treatment status of the cat (being treated or not treated) at the time of sampling.…”
mentioning
confidence: 99%